Strategic approach to investment portfolios through the prism of precious metals - Martina Marinac; Marija Vukoja (UTMS Journal of Economics, 2022)
Within finance, there is an area of investment based on the role in investment opportunities that are expected to increase in value in the short or long term, further to this, will also increase a profit for the investor. Depending on preferences, risk propensity and available trading facilities, investors make decisions about the components of their own investment portfolios. The general premise on the basis of which investors decide is to make as much profit as possible, and at the lowest possible rate of risk. In order to meet this unwritten rule, investors must focus their investments on more investment options, which is diversify of the investment portfolio; what is also what modern portfolio theory, or Markowitz's theory, is about. In this way, the risk is allocated to several smaller segments or investment options and potentially achieves a higher return on investment than would be realized if all available funds were directed to one investment object. Diversification, in practice, serves as an effective investment tool that provides the investor a protection against risk, but it is also a tool to achieve the basic goal of investment, or profit for which the investor stands.
Keywords: F01; Z32; 330; investment; portfolio; precious metals; diversification; modern portfolio theory